PENGARUH PENGETAHUAN PERPAJAKAN, KESADARAN WAJIB PAJAK, SISTEM E-SAMSAT DAN INSENTIF PAJAK TERHADAP KEPATUHAN PEMBAYARAN PAJAK KENDARAAN BERMOTOR DI KABUPATEN KLATEN - Mahapsari, Mardina Mey; Yustrianthe, Rahmawati Hann; Purwantini, Maria; Asmarawati, Budi (Universitas Riau Kepulauan, 2024)
This study aims to determine the effect of tax knowledge, taxpayer awareness, E-samsat system, tax incentives on compliance with motor vehicle tax payments in Klaten Regency. The population used in this study were taxpayers in Klaten Regency. The sample selection in this study used the Purposive Sampling method and obtained a sample of 100 respondents. The data analysis technique used multiple linear regression analysis. The results of the study showed that tax knowledge and taxpayer awareness had an effect on taxpayer compliance, while the e-samsat system and tax incentives did not have an effect on taxpayer compliance.